COMPARATIVE EVALUATION OF NATIVE DUCKS OF ORISSA, KHAKI CAMPBELL AND THEIR CROSSES IN EXTENSIVE SYSTEM OF REARING (Indian Journal of Animal Production and Management, 2014)
This study was undertaken to evaluate the production performance of native ducks of Orissa (Deshi), Deshi × Khaki Campbell cross and Khaki Campbell in extensive system of rearing. A total of 200 Deshi, 140 crosses of Deshi (male) × Khaki Campbell (female) (DK) and 160 Khaki Campbell ducklings produced in single hatch were distributed to the farmers, 20 number each at costal part of Cuttack district of Orissa. All the ducklings were brooded in deep litter system at farmer’s field with normal brooding management and feeding. Body weights of the ducks at 2nd, 4th, 6th, 8th and 40th week of age obtained in three genetic groups revealed that crossbred (DK) perform better and grow faster than the Desi and Khaki Campbell in extensive system of rearing. Duck day egg production per bird at different age in crossbred is intermediate compared to Deshi and Khaki Campbell. The age at first egg of the flock and age at 50 % duck day egg production is better in the present study.
Keywords: Khaki Campbell; extensive system; genetic group